A Comparative Analysis of Board Qualities and Performance of Listed Deposit Money Banks in Nigeria and Ghana - Oluwagbade, Oluyinka; Awotomılusı, Niyi Solomon; Dada, Samuel Ajibade; Abe, Temitayo Oluwatimilehin; Adewara, Motunrayo Olayinka (International Review of Management and Marketing, 2024)
Disclosure of board information is crucial for good governance, risk management, and stakeholder relations in the banking sector. The board of directors’ quality is crucial in setting strategic direction and ensuring effective governance. This study comparatively examined the qualities of the board of directors of listed deposit banks in Nigeria and Ghana and assessed the effects of the board qualities on the financial performance of banks in the two countries. The study used an ex post facto research design, involving 19 deposit money banks listed on the Nigerian Exchange Limited and Ghanaian Stock Exchange. Data was collected from audited annual reports and analyzed using descriptive and inferential statistics. The descriptive analysis includes mean, median mode, minimum, and maximum among others while the inferential analysis includes independent t-tests and panel regression. The study reveals that the board of listed deposit money banks in the Nigerian exchange group meets more frequently and is more independent than those in the Ghanaian stock exchange, and their board size is larger than in Ghana. Board female gender diversity of listed deposit money banks on the Nigerian exchange group is not significantly lower than the board female gender diversity of firms listed on the Ghanaian stock exchange. The study reveals that board gender diversity doesn’t significantly impact the financial performance of listed deposit money banks in Nigeria and Ghana. However, board independence has a negative effect in Nigeria, while board meetings negatively affect performance in Nigeria. Board size also has a positive effect in Nigeria. The study recommends that directors of listed banks in Nigeria should reduce the number of their meetings or expenses of the meeting because it is reducing the profitability of the companies. The study also recommends that the banks in Ghana should provide regular training for independent directors to enhance their understanding of the industry.